The Many Faces Of Tsai Ming-liang: Cinephilia, The French Connection, And Cinema In The Gallery - Tsai, Beth (Penerbit Universiti Sains Malaysia (USM Press), 2017)
The Malaysia-born, Taiwan-based flmmaker Tsai Ming-liang's Visage (2009) is a flm that was commissioned by the Louvre as part of its collection. His move to the museum space raises a number of questions: What are some of the implications of his shift in practice? What does it mean to have a flm, situated in art galleries or museum space, invites us to think about the notion of cinema, spatial confguration, transnational co-production and consumption? To give these questions more specifcity, this article will look at the triangular relationship between the flmmaker's prior theatre experience, French cinephilia's inﬂuence, and cinema in the gallery, using It's a Dream (2007) and Visage as two case studies. I argue Tsai's flm and video installation need to be situated in the intersection between the moving images and the alternative viewing experiences, and between the global and regional flm cultures taking place at the theatre-within-a-gallery site. While Tsai's slow flm aesthetics can be traced in relation to his prior theatre practice, his installation and flm in the gallery are grounded in the belief that cinema needs to be resurrected in the museum. The interrelations between Tsai's video installation and feature flms show that they originate from, and are still part of, love for cinema. Tsai's move to the museum space exemplifes the possibility for the future of cinema: it may lose its exclusivity of the collective experience in the movie theatre, yet still privileges the architectural situation of cinema.